Guías para la vacunación de perros (caninos) y gatos (felinos) en Perú - Rubio, Alicia (2018)
The Peruvian Committee of COLAVAC has prepared this vaccination guide for the Peruvian veterinarian to be used as a tool in the design of vaccination schedules for dogs and cats, based on risk analysis, presence of endemic diseases and characteristics of vaccines currently available in Peru. The document present recommendations for vaccination schedules with essential vaccines as well as those of optional use. Vaccination is a medical act, so the final decision must be made by the clinician considering in addition to the factors mentioned above, the characteristics of each patient including the risk/benefit of immunization. In each case, the vaccination strategy should be discussed with the owner so that the owner can make an informed decision.